2018
DOI: 10.1101/388512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MAP7 family proteins regulate kinesin-1 recruitment and activation

Abstract: Kinesin-1 is responsible for microtubule-based transport of numerous cellular cargoes. Here, we explored the regulation of kinesin-1 by MAP7/ensconsin family proteins. We found that all four mammalian MAP7 family members bound to kinesin-1, and MAP7, MAP7D1 and MAP7D3 acted redundantly to enable kinesin-1-dependent transport in HeLa cells. Microtubule recruitment of the truncated kinesin-1 KIF5B-560, which contains the stalk but not the cargo-binding and autoregulatory regions, was inhibited in cells co-deplet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(102 citation statements)
references
References 46 publications
10
90
1
1
Order By: Relevance
“…In a similar manner, other MAPs such as MAP1B [109], MAP2, MAP4 [110,111], MAP6 [112] and MAP7 [113][114][115][116] were shown to influence intracellular transport but perhaps not with the same selectivity (Fig. 3F).…”
Section: Physiological Functions Of Mapsmentioning
confidence: 64%
“…In a similar manner, other MAPs such as MAP1B [109], MAP2, MAP4 [110,111], MAP6 [112] and MAP7 [113][114][115][116] were shown to influence intracellular transport but perhaps not with the same selectivity (Fig. 3F).…”
Section: Physiological Functions Of Mapsmentioning
confidence: 64%
“…Thus, this unique microtubule binding property of MAP7, likely mediated by peptides outside the N domain, provides a novel mechanism to regulate microtubule stability in neurons. As recent work (Hooikaas et al, 2019;Pan et al, 2019) reported diverse functions of mammalian MAP7 homologs, it would thus be interesting to determine whether these homologs have similar microtubule binding properties as MAP7.…”
Section: Map7 Promotes Stable Microtubules In Mature and Nascent Branmentioning
confidence: 99%
“…The binding rate of the motor is k on = π 0 microtubule within reach 0 microtubule not within reach (5) The microtubule is within reach of the motor if the distance between the location of the anchor and any point on the surface of the microtubule is less than the motor length away and the motor would not have to go through the bead to reach it. Motors are allowed to bind if the motor could reach around the surface of the bead to the surface of the microtubule.…”
Section: Cargo Simulationmentioning
confidence: 99%
“…At a single-molecule level, motor behavior involves attachment to the microtubule, stepping, and detachment from the microtubule. While the stepping and detachment processes have been extensively studied -including under load in backward, forward [1], left, right [2], and upward [3] directions, and as modified by MAPs [4,5] and tubulin state [6] -the attachment rate is less well-understood.…”
Section: Introductionmentioning
confidence: 99%